Distribution, abundance, and diversity of microplastics in the upper St. Lawrence River. (May 2020) - Crew, Alex; Gregory-Eaves, Irene; Ricciardi, Anthony
Abstract: Microplastics are pervasive pollutants in fresh waters, but their distribution, abundance, and diversity in fluvial environments remain poorly documented. Previous research indicated that large polyethylene microbeads were abundant in the freshwater sediments of the St. Lawrence River. Here we extend this work by quantifying the abundance of a broad range of sizes and types of microplastics in sediments and surface water samples, and we relate these metrics to environmental variables. We sampled 21 sites for sediments that spanned a land use gradient, and 10 surface water stations above and below wastewater effluent sites, along the fluvial corridor of the St. Lawrence River between Montreal and Quebec City from July to August 2017. Microplastics were removed from sediments using an oil extraction protocol and enumerated under fluorescent microscopy. We tested predictions that environmental filters and known point sources affect microplastic concentrations in the river. The mean concentration of microplastics across all sediment sampling sites was 832 (±150 SE) plastics per kg dry weight (range 65–7562 plastics per kg dry weight), which is among the highest recorded (in the top 25%) for the world's freshwater and marine systems. Microplastic concentrations in the sediments were significantly related to a suite of environmental variables including land use and sediment particle characteristics. Particle characteristics, proximity to point sources (urban land use), and environmental filters (sediment compositional variables, % organic carbon, % inorganic carbon and distance from shore) each explained a significant fraction of variation in the microplastic composition in the sediment, with environmental filters having the greatest influence. We present a protocol that could be used to efficiently and accurately detect a broad range of microplastics until a standardized protocol is established for large-scale monitoring. Graphical abstract: Image 1 Highlights: Microplastic beads, fibres and fragments were quantified in sediments and surface waters of the St. Lawrence River. Concentrations of microplastics in sediments ranged from 65 to 7561 (mean = 832) items·kg dry weight −1 . Mean concentration of microplastics was among the highest recorded for any aquatic system. Environmental filters, point sources and sediment characteristics influenced microplastics distribution across the river bed.